The Effect of Naoh for Sugarcane Bagasse Reinforced Alumina Composite to their Mechanical Properties - NURAINA NAZIFA BINTI AZRUL EFFENDY; Mohamad, Zaleha (Research Progress in Mechanical and Manufacturing Engineering, 2025)
The use of natural fiber-reinforced composites has gained momentum as a sustainable solution for reducing environmental impact and material cost in engineering applications. This study investigates the mechanical properties of sugarcane bagasse (SCB) reinforced alumina composites using Unsaturated Polyester Resin (UPR) as the polymer matrix, focusing on the effect of alkali treatment with sodium hydroxide (NaOH). Composites were fabricated with varying SCB and alumina contents, with and without 5% NaOH-treated fibers, to evaluate tensile and flexural behavior according to ASTM standards. The results demonstrated that NaOH treatment significantly improved fiber-matrix interfacial bonding, resulting in enhanced mechanical performance. Among all tested compositions, the treated sample with 3% SCB, 12% alumina, and 85% UPR exhibited the highest improvement in both tensile and flexural strength, attributed to effective stress transfer and optimal dispersion of reinforcement. The findings affirm the potential of chemically treated agro-waste fibers and ceramic fillers to produce high-performance, eco-friendly composites suitable for structural and semi-structural applications.